NILAI-NILAI PENDIDIKAN DALAM PERSPEKTIF ALQURAN SURAT ‘ABASA - Zulkarnen, Syamsu Nahar, Zulheddi (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2018)
Abstrack: The purpose of this research is to find out how is the interpretation of ‘Abasa on education offaithful, worship, moral attitude and social. The education’s moral value and the relevant This researchused the qualitative method or based on the study library. The first final result is the interpretation of al-Misbah was started by explanation then spelled the obstacle words into the explanation. Ibnu Katsirbook was started the explanation by hadis. And ibnu katsir’s book no obstacle words. Al-Maraghi’sbook was started by the obstacle words interpreted. Al-Khazin’s book was started by the explanation ofasbab al-wurud and then seeing theasbab an-Nuzul. The noble Quran by ministerial religion affair wasstarted by words. Buya Hamka no finding the words, but was started by the explanation andmafatihual-Ghaib was told by Allah, is admonishes Muhammad saw was sullen face and avoided from Abdullahbin Ummi Maktum was blind. And the education’s moral value here are the education of social, theteacher must be in justice fair, ibadah education must be takwa to Allah swt, the akidah/faithful educationis believe full to Allah, and the moral value education provided the moral award similar to. Therelevant of this verse is creating the students must be taken a worship to Allah, syahadah to Allah, politeand polite to the parents, teachers and others.Tujuan penelitian ini adalah untuk mengetahui bagaimana penafsiran surat ‘Abasa dalam pendidikanakidah, ibadah, akhlak dan sosial. Nilai-nilai pendidikannya serta relevansinya. Penelitian ini menggunakanmetode kualitatif atau penelitian bersifat studi pustaka. Hasil penelitian pertama bahwa penafsiran bahwapenafsiran Tafsiral-Misbah dimulai dengan penjelasan kemudian menyebutkan kata-kata sulit untuk kedalam penjelasan. Tafsir Ibnu Katsir dimulai dengan penjelasan kemudian diberi hadis-hadis Tafsir IbnuKatsir ini tidak terdapat kosa kata sulit. Tafsiral-Maraghi dimulai dengan penafsiran kata-kata sulit. Tafsiral-Khazin dimulai dengan penjelasanasbab al-Wurudnya. Dan melihatasbab an-Nuzul nya. Tafsir Alquranoleh Kementerian Agama Republik Indonesia dimulai dengan kosa kata. Tafsir al-Azhar karya BuyaHAMKA tidak terdapat kosa kata, dimulai dengan penjelasan dan TafsirMafatihu al-Ghaib mengenaiayat ini Allah swt. menegur Nabi Muhammad saw. yang bermuka masam dan berpaling dari Abdullahbin Ummi Maktum yang buta. Nilai-nilai pendidikannya adalah pendidikan sosial guru harus adil, pendidikanibadah takwa kepada Allah swt. pendidikan akidah meyakini kebenaran Allah, dan pendidikan akhlakmemberi penghargaan sesama. Relevansinya adalah menjadikan anak didik takwa kepada Allah, bersyahadahkepada Allah, patuh dan sopan kepada orang tua, guru dan yang dituakan.Kata Kunci: Nilai Pendidikan, Alqur’an, ‘Abasa